Enraizamento de estacas de Trichilia catigua A. Juss (catigua) em diferentes estações do ano - Valmorbida, Janice; Boaro, Carmen Sílvia Fernandes [UNESP]; Lessa, Antonio Oliveira; Salerno, Airton Rodrigues (Sociedade de Investigações Florestais, 2008)
Pertencente à família Meliaceae, Trichilia catigua A. Juss possui casca com propriedades adstringente, inseticida, purgativa, tônica, bactericida, antiinflamatória e antidepressiva. Este estudo objetivou enraizar estacas de ramos lenhosos da espécie em diferentes estações do ano. Para tal, estacas com aproximadamente 15 cm de comprimento, coletadas de árvores adultas, foram preparadas da parte apical e mediana dos ramos e submetidas aos reguladores vegetais AIB (ácido indolbutírico), ANA (ácido naftalenoacético) e AIA (ácido 3-indolacético). Determinaram-se a porcentagem de estacas enraizadas e mortas e, quando enraizadas, seu comprimento e diâmetro. Na primavera de 2004, as estacas foram submetidas às concentrações de 1.000 e 2.000 mg L-1 de AIB, ANA e AIA e avaliadas aos 90 dias. As maiores porcentagens de enraizamento foram iguais a 33,33; 25,00; 22,91; e 23,43%, respectivamente com AIB 1.000, 2.000 mg L-1 e ANA 1.000 e 2.000 mg L-1. No verão, outono, inverno e primavera de 2005 os experimentos foram conduzidos com AIB, ANA e AIA nas concentrações de 1.000, 2.000 e 3.000 mg L-1, sendo as avaliações realizadas aos 120 dias. A maior porcentagem de enraizamento, igual a 19,17%, foi obtida com AIB 3.000 mg L-1. Na primavera de 2006 foram testadas as doses iguais a 1.000, 2.000, 3.000, 4.000 e 5.000 mg L-1 de AIB e 1.000, 2.000 e 3.000 mg L-1 de ANA. A maior porcentagem de enraizamento, 41,67%, foi obtida com a utilização de 5.000 mg L-1 de AIB.

Trichilia catigua A. Juss contains substances with astringent, insecticidal, purgative, tonic, bactericidal, anti-inflammatory and anti-depressive properties in its barks. This study aimed at rooting of hardwood cuttings of this species in different seasons. Stem cuttings -about 15 cm long- were collected from adult trees and were prepared from the apical and medial part of the branches. The cuttings were treated with the plant regulators AIB (indole-3-butyric acid), NAA (naphthalene acetic acid) and IAA (indole-3-acetic acid). The percentage of rooted or dead stem cuttings was determined; when rooting was successful, length and diameter were measured. In the spring of 2004 stem cuttings were treated with concentrations of 1000 and 2000 mg L-1 of IBA, NAA and IAA and evaluated after 90 days. The greatest rooting percentages were 33.33, 25.00, 22.91 and 23.43% with IBA 1000, 2000 mg L-1 and NAA 1000 and 2000 mg L-1, respectively. In the summer, fall, winter and spring of 2005 the experiments were carried out with IBA, NAA and IAA in the concentrations of 1000, 2000 and 3000 mg L-1 and the evaluations done at 120 days. The higher rooting percentage, 19.17%, was obtained with IBA at 3000 mg L-1. In the spring of 2006 IBA at doses 1000, 2000, 3000, 4000 and 5000 mg L-1, and NAA at 1000, 2000 and 3000 mg L-1 were tested. The greatest rooting percentage was 41.67%, and was obtained with the use of 5000 mg L-1 of AIB.
Rooting of Trichilia catigua A. Juss (catigua) stem cuttings in different seasons of the year
Keywords: Ácido indolbutírico; planta medicinal; estaca lenhosa; Indole-3-butyric acid; medicinal plant; wood cutting